THE EFFECT OF PROFIT MANAGEMENT, TAX PLANNING, TAX AVOIDANCE ON COMPANY VALUE (EMPIRICAL STUDY OF BASIC AND CHEMICAL INDUSTRIAL MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE, 2018-2021) - Bestar, Sarah Cantika; Damayanty, Prisila (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to examine the effect of earnings management, tax planning, and tax avoidance on firm value. The population of this research is manufacturing companies in the basic and chemical industry sub-sectors that are listed on the Indonesia Stock Exchange (IDX) for 2018 – 2021. The sample for this study used a purposive sampling method so as to obtain a sample of 8 companies as research samples. This analytical method uses multiple linear regression analysis with SPSS 26. The results of this study indicate that earnings management and tax planning have no significant negative effect on firm value, while tax avoidance has a significant negative effect on firm value. And earnings management, tax planning and tax avoidance simultaneously have a significant positive effect on firm value. Keywords: earnings management, tax planning, tax avoidance and firm value